Entre la Madre Chingada y la Mexica violada : uma reflexão decolonial, antipatriarcal e iconográfica de Malintzin - Pereira, Walquíria Rodrigues. (UFRJ, 2021)
[PT] Esta Dissertação, concentrada na área de Estudos Literários Neolatinos/Literaturas Hispânicas e na linha de pesquisa Poéticas, História e Crítica consiste num estudo acerca de Malintzin, a mulher náhuatl que atuou como intérprete e “concubina” do “conquistador” Hernán Cortés durante a invasão do território hoje conhecido como México. Malintzin tornou-se uma personagem emblemática, ora tida como amante e traidora, ora tida como mulher refém da invasão espanhola. É observada, de acordo com o pensamento decolonial e antipatriarcal, como sua figura é descrita no romance histórico Malinche (2006), de Laura Esquivel, com ilustrações em forma de códice. A metodologia se apresenta na leitura do romance em seu caráter narrativo pela escrita de Esquivel e iconográfico pelas ilustrações de Jordi Castells - que compõem a obra -, em contraste com as representações iconográficas de Malintzin nas pinturas: O sonho da Malinche, de Antonio Ruíz (1892-1964); A noite triste e Hernán Cortés e Malinche, de Jesús Helguera (1910-1971); Cortés e Malinche, de José Clemente Orozco (1883-1949); e O encontro de Moctezuma II e Cortés e Malinche com Cortés, de Roberto Cueva del Río (1908-1988), sendo possível questionar as ideologias que permeiam a imagem da mulher mexica subalternizada.Malintzin é unificada à palavra castelhana que se espalhou na América (ROBLES, 2019), pelo fato de ter atuado, ainda que indiretamente, com os espanhóis na invasão do México. Assim, é interessante pensar sua figura em diálogo com os estudos críticos de Enrique Dussel (1999) e León-Portilla (2003; 2012), que evidenciam a perspectiva dos vencidos na conquista; Milagros Palma (1991), Margo Glantz (1995; 2001) e Cristina González (2002), por revisitarem Malintzin do ponto de vista histórico e teórico e a sua influência no discurso nacionalista mexicano; Aníbal Quijano (1991; 2005) e Catherine Walsh (2005), por trazerem uma reflexão sobre o pensamento decolonial, acrescido das discussões sobre gênero propostas por Maria Lugones (2020), entre outros. O ato de revisitar a figura de Malintzin de modo decolonial desconstrói o discurso histórico de culpa e submissão.[EN] This Dissertation, concentrated in the area of Neolatin Literary Studies/Hispanic Literatures and in the line of research Poetics, History and Criticism, consists of a study about Malintzin, the náhuatl woman who acted as an interpreter and “concubine” of the “conqueror” Hernán Cortés during the invasion of territory now known as Mexico. Malintzin became an emblematic character, sometimes considered a lover and a traitor, sometimes considered a woman hostage to the Spanish invasion. It is observed, according to the decolonial and anti- patriarchal thinking, how his figure is described in the historical novel Malinche (2006), by Laura Esquivel, with illustrations in the forms of a codex. The methodology is presented in the reading of the novel in its narrative character by the writing of Esquivel and iconographic by illustrations of Jordi Castells – that make up the work -, in contrast to Malintzin’s iconographic representations in the paintings: Malinche's dream, by Antonio Ruíz (1892- 1964); The sad night and Hernán Cortés and Malinche, by Jesús Helguera (1910-1971); Cortés and Malinche, by José Clemente Orozco (1883-1949); and The encounter of Moctezuma II and Cortés and Malinche with Cortés, by Roberto Cueva del Río (1908-1988), being possible to question the ideologies that permeate the image of subalternized mexican women.Malintzin is unified with the Spanish word that spread in America (ROBLES, 2019), for having acted, albeit indirectly, with the Spaniards in the invasion of Mexico. So it is interesting to think of your figure in dialogue with the critical studies of Enrique Dussel (1999) and León-Portilla (2003; 2012), which highlight the perspective the losers in the conquest; Milagros Palma (1991), Margo Glantz (1995; 2001) and Cristina González (2002), for revisiting Malintzin from a historical and theoretical point of view and her influence on mexican nationalist discourse; Aníbal Quijano (1991; 2005) and Catherine Walsh (2005), for bringing a reflection on decolonial thinking, in addition to the discussions on gender proposed by Maria Lugones (2020), among others. The act of revisiting the figure of Malintzin in a decolonial way deconstructs the historical discourse of guilt and submission.